2018
DOI: 10.5489/cuaj.5032
|View full text |Cite
|
Sign up to set email alerts
|

How long do we have to treat overactive bladder syndrome? A questionnaire survey of Canadian urologists and gynecologists

Abstract: Introduction: Overactive bladder syndrome (OAB) is a highly prevalent and costly condition worldwide with negative impact on health-related quality of life. Although many guidelines exist and anticholinergics are considered to be the mainstay of pharmacological treatment, data are lacking regarding optimal treatment duration. Therefore, the aim of this study was to determine practice patterns of Canadian urologists and gynecologists regarding duration of OAB pharmacotherapy. Methods: A 14-question survey was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…According to Basra et al, 16 no recommendations for the treatment duration for OAB have been published, and the lack of understanding of the natural history of OAB makes it difficult to provide a definite recommendation regarding the optimum therapy duration required. More recently, Przydacz et al 18 also stated that no consensus has been reached on the optimal duration of OAB treatment and that the resolution of bothersome symptoms has been considered as one of the most common reasons for treatment termination and may be achieved in more than one‐third of OAB cases. They conducted a questionnaire survey to determine the practice patterns of urologists and gynecologists on the OAB pharmacotherapy duration.…”
Section: Discussionmentioning
confidence: 99%
“…According to Basra et al, 16 no recommendations for the treatment duration for OAB have been published, and the lack of understanding of the natural history of OAB makes it difficult to provide a definite recommendation regarding the optimum therapy duration required. More recently, Przydacz et al 18 also stated that no consensus has been reached on the optimal duration of OAB treatment and that the resolution of bothersome symptoms has been considered as one of the most common reasons for treatment termination and may be achieved in more than one‐third of OAB cases. They conducted a questionnaire survey to determine the practice patterns of urologists and gynecologists on the OAB pharmacotherapy duration.…”
Section: Discussionmentioning
confidence: 99%
“…This observation may be explained in two different ways. Whereas treatment for LUTS in men typically includes alpha-blockers or 5-alpha-reductase inhibitors with mild side effect profiles, treatment of LUTS in women often includes anticholinergics, with significant dropouts because of adverse events [ 29 ]. Alternatively, until now, public urological campaigns in Poland have been focused mainly on men, and women might be inadequately targeted.…”
Section: Discussionmentioning
confidence: 99%
“…A Canadian group sought to investigate the practices utilized by urologists and gynecologists regarding the treatment of OAB (38). In the survey, the study found that 52% versus 45% of urologists, and gynecologists stated that its treatment should be time defined rather than lifelong.…”
Section: Physician Perspectivementioning
confidence: 99%